Factors affecting the surgeon preference for bolus opioid use to control postoperative pain after bariatric surgery - Zengin, Seniyye; Ergün, Meliha; Taşkın, Halit (Journal of Surgery and Medicine, 2021)
Background/Aim: Pain control after bariatric surgery is important and inadequate control may lead to unwanted consequences. Although opioids remain an important therapeutic option in the management of postoperative pain, recent observations have pointed out to an increasing reluctance of surgeons to use opioid centered acute pain management strategies. This study aimed to examine the attitude and practice among bariatric surgeons regarding the postoperative use of opioids in acute pain management. Methods: Sixty-seven surgeons actively involved in surgery for obesity and metabolic disorders who responded to a survey questioning their practical habits for postoperative pain management were included in this cross-sectional study. The questionnaire had a total of 16 multiple-choice questions on postoperative pain management. Potential factors affecting their preference for postoperative bolus opioid use were examined. Results: Twenty-seven surgeons (40.3%) indicated that they prefer bolus opioid doses for postoperative analgesia. Surgeon age >55 years emerged as the only significant independent predictor for not preferring bolus postoperative opioid (OR: 0.19, 95% CI: 0.04-0.91, P=0.039). Main concern for opioid use was respiratory depression reported by 34.3% of the surgeons. Tramadol was the most preferred opioid (68.7%). Conclusion: Relatively low number of bariatric surgeons seems to prefer bolus opioid administration after bariatric surgery to control acute postoperative pain. Older bariatric surgeons (>55 years of age) seem more reluctant. However, opioids, which should be used with caution in such patients with obesity, may be an option after bariatric surgery in selected patients.